Horizontal Distribution of Salinity and Temperature on Merbok Estuary, Malaysia - Muhammad Syukri (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2009)
Telah dilakukan studi mengenai karakteristik dan distribusi salinitas dan temperatur dan water system di estuaria Merbok dan di sekitar perairan pantai. Penelitan ini difokuskan pada proses-proses fisika. Hasil analisis menunjukkan suatu pola variabilitas khusus mengenai fenomena yang terjadi secara horizontal. Pada kondisi debit air (discharge) yang tinggi, air dengan salinitas (isohalines) rendah akan terdapat di dekat mulut sungai. Pada kondisi debit air rendah, keberadaan air sungai mengisi lebih jelas di estuaria bagian bawah. Pola yang sama juga teramatiuntuk parameter temperatur di daerah yang sama yang disebabkan rendahnya debit sungai. Dengan debit yang lebih tinggi dapat menyebabkan perubahan temperatur air payau dibandingkan debit yang lebih rendah. Hal ini menyebabkan terjadi proses transisi stratifikasi antara debit air yang tinggi dan rendah tersebut.Kata kunci: debit sungai (discharge), salinitas, temperatur, perairan pantai, estuaria. The characteristics and distribution of the salinity and temperature and water systems in the Merbok Estuary and nearby coastal waters are examined. This research focuses mainly on physical processes. The results analysis provides an insight the typical scales of variability of the horizontal phenomena. During high discharges, the lower salinity water (isohalines) was more evident near the estuary mouth due to high discharge. During low discharge, the invasion of freshwater in the lower estuary was much less pronounced. Similar temperature trend was observed for the estuary possibly due to low discharge phenomenon. Bigger amount of freshwater can dictate the brackish water temperature compare to smaller amount of freshwater. There was a transition in stratification between high and low river discharge.  Key words : river discharge; salinity; temperature; coastal water; estuary